Distributive Justice, Job Satisfaction and Ethical Leadership Effect On Employee Organizational Commitment - Didik Purwiyanto; FX Adi Purwanto (Wacana Journal of Social and Humanity Studies, 2021)
This research is motivated by an organization or company success whose biggest factors are influenced by employee performance. This study used employee respondents of PT Pelindo III (Persero) Tanjung Perak Port Surabaya which consist of 225 respondents taken using accidental sampling techniques. Data analysis using multiple linear analysis. The results showed that fair distribution, job satisfaction, and ethical leadership influenced the organization's committee. This is influenced by several factors, such as companies that can allocate rewards appropriately, employees who are satisfied with the work they do and the existence of organization leaders or companies that can to be exemplary and motivating.